Tomb families : private tomb distribution in the New Kingdom Theban Necropolis - Slinger, Katherine (Archaeopress Egyptology, 2022)
'Tomb Families' investigates the apparently random distribution of New Kingdom private tombs in the Theban Necropolis by focusing on factors that may have influenced tomb location. This research provides a deeper understanding of the necropolis and how private tombs linked to the wider sacred landscape of Thebes.